2013
DOI: 10.14742/ajet.174
|View full text |Cite
|
Sign up to set email alerts
|

Validating and modelling technological pedagogical content knowledge framework among Asian preservice teachers

Abstract: The Technological Pedagogical Content Knowledge (TPCK) framework has been adopted by many educational technologists and teacher educators for the research and development of knowledge about the pedagogical uses of Information and Communication Technologies (ICT) in classrooms. While the framework is potentially very important, efforts to survey teachers' TPCK efficacy has yet to identify all seven factors postulated by the framework. This study attempted to validate a TPCK efficacy survey by implementing it on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
150
1
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(174 citation statements)
references
References 29 publications
8
150
1
15
Order By: Relevance
“…This step should be very clear and explicit to ensure full integrating of the domains. As the results of this study and the others (e.g., Chai et al, 2013b) TPK is more related to TPACK-SE, hence, more emphasis may be put on it. In the next step, content-specific highlights would be useful in developing TPACK-SE.…”
Section: Implications For Science Teacher Educationsupporting
confidence: 55%
See 2 more Smart Citations
“…This step should be very clear and explicit to ensure full integrating of the domains. As the results of this study and the others (e.g., Chai et al, 2013b) TPK is more related to TPACK-SE, hence, more emphasis may be put on it. In the next step, content-specific highlights would be useful in developing TPACK-SE.…”
Section: Implications For Science Teacher Educationsupporting
confidence: 55%
“…Yet another research conducted with pre-service teachers, Chai, et al, (2013b) found that TK, CK, and PK did not have direct relationships with TPACK while there was an indirect relationship between TK and TPACK (through both TCK and TPK). TCK served as the mediator for the relationship between CK and TPACK.…”
Section: Interrelationships Among Knowledge Types Of Tpackmentioning
confidence: 92%
See 1 more Smart Citation
“…In the development of TPACK assessment instruments, pedagogy-, content-and technology-specific questionnaires seems to replicate most strongly the original TPACK structure (e.g. Chai et al, 2013;Koh et al, 2013;Valtonen et al, 2015).…”
Section: Measuring Tpack With Questionnairesmentioning
confidence: 98%
“…Koehler ve Mishra (2005) tarafından geliştirilen teknolojik pedagojik içerik bilgisi (TPAB) kuramsal çerçevesini temel alan araştırmacılar, geçtiğimiz on yıllık süreçte öğretmenlerin TPAB yeterlilikleri, kurucu faktörleri ve yapısal ilişkileri ölçmek için çeşitli araçları incelemiş ve geliştirmiştir (Akman ve Güven, 2015;Chai, Ng, Li, Hong ve Koh, 2013;Canbazoğlu Bilici, Yamak, Kavak ve Guzey, 2013;Koh, Chai ve Tsai, 2010;Schmidt vd., 2009). Bu ölçüm araçlarının, öğretmenlerinin profesyonel gelişimlerine yardımcı olma ve öğretmen eğitimi ve öğretim programları için kurs içeriğini ve pedagojik yöntemleri iyileştirme konusunda oldukça etkili olduğu ve çok önemli bilgiler verdiği kanıtlanmıştır.…”
Section: Introductionunclassified